2020
DOI: 10.1002/prp2.665
|View full text |Cite
|
Sign up to set email alerts
|

Impact ofCYP2C19,CYP3A4,ABCB1, andFMO3genotypes on plasma voriconazole in Thai patients with invasive fungal infections

Abstract: Voriconazole is the first‐line antifungal choice in the treatment of invasive fungal infections (IFIs). Single nucleotide polymorphisms (SNPs) in drug‐metabolizing and transporter genes may affect voriconazole pharmacokinetics. This study aimed to determine the frequency of the CYP2C19 rs4244285, rs4986893, rs72552267, and rs12248560, CYP3A4 rs4646437, ABCB1 rs1045642, and FMO3 rs2266782 alleles and determine the associ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 38 publications
3
10
0
Order By: Relevance
“…In this study, the allele frequency of CYP3A4 rs4646437 was 30.9%, but no significant difference in voriconazole plasma levels between the noncarriers and carriers. Our results corroborate a report by Chuwongwattana et al [33]. In agreement with a previous study involving 86 Chinese subjects [34], the CYP3A4*22 allele carriers were not observed in this research.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…In this study, the allele frequency of CYP3A4 rs4646437 was 30.9%, but no significant difference in voriconazole plasma levels between the noncarriers and carriers. Our results corroborate a report by Chuwongwattana et al [33]. In agreement with a previous study involving 86 Chinese subjects [34], the CYP3A4*22 allele carriers were not observed in this research.…”
Section: Discussionsupporting
confidence: 93%
“…Our results corroborate a report by Chuwongwattana et al . [33]. In agreement with a previous study involving 86 Chinese subjects [34], the CYP3A4*22 allele carriers were not observed in this research.…”
Section: Discussionsupporting
confidence: 93%
“…Various methods have been suggested for the analysis of the targeted SNPs. For example, FMO3-related SNPs were detected by PCR-restriction fragment length polymorphism [24], real-time PCR [25], or direct sequencing methods [26]. The automated sequencing method was rst introduced in the 1970s by Frederick Sanger [27].…”
Section: Resultsmentioning
confidence: 99%
“…Various methods have been proposed to analyze the targeted SNPs. For example, FMO3 -related SNPs have been detected by using PCR-restriction fragment length polymorphism analysis ( 19 ), real-time PCR ( 20 ) and direct sequencing methods ( 21 ). Sequencing technology was first conceptualized and developed in the 1970s by Sanger et al ( 22 ).…”
Section: Discussionmentioning
confidence: 99%
“…FMO3 genetic polymorphisms have been the focus of considerable interest in research; these findings can be applied to various studies on the pharmacokinetics of various medications, including anti-diabetics (e.g., teneligliptin) ( 5 , 6 ), antibiotics (e.g., voriconazole) ( 20 , 25 ) and non-steroidal anti-inflammatory drugs (e.g., sulindac) ( 4 , 13 , 14 ), as well as human diseases, such as cardiovascular disorders ( 2 , 7 ). FMO3 increases plasma trimethylamine N-oxide (TMAO) levels by catalyzing the conversion of trimethylamine (TMA) derived from the gut microbiome ( 26 , 27 ).…”
Section: Discussionmentioning
confidence: 99%